SnO2 decorated SiO2 chemical sensors: Enhanced sensing performance toward ethanol and acetone. (September 2017) - Asgari, Mehrdad; Saboor, Fahimeh Hooriabad; Mortazavi, Yadollah; Khodadadi, Abbas Ali
Abstract: SnO2 decorated SiO2 chemical sensors with different Sn/Si ratios were synthesized by micro-emulsion followed by ultrasonic-assisted deposition-precipitation method and used for highly sensitive and selective detection of ethanol and acetone. XRD, EDS, SEM, and TEM were used to characterize the samples. The results confirm deposition of small crystalline tin oxide particles on the surface of silica particles. Using these formed materials for detection of ethanol and acetone resulted in significant enhancement of the sensitivity and reducing temperature of maximum response in comparison to the pure SnO2 . The selectivity of the sample with the highest sensitivity to ethanol and acetone, i.e. 80 wt% SnO2 /SiO2, was examined by measuring its sensitivity to some interfering gases including carbon monoxide, methane, toluene, Trichloroethylene (TCE) and propane; the results showed very high selectivity of the sensor to ethanol and acetone, especially at low temperatures. The sensor responses to traces of acetone in the air with the concentration ranging from 0.5 to 5 ppm at different temperatures of 70, 170 and 270, and 370 °C were measured to evaluate the capability of the sensor for detection of acetone in the breath of human, which is helpful in the diabetes diagnosis. The sensor could effectively show high enough sensitivity even to these very low concentrations of acetone which reveals its high potential for being used in acetone detection devices. Finally, the effect of humidity on the sensitivity of sensor to acetone was investigated. Increasing the humidity of background air, caused the sensor response to decrease and the operating temperature of maximum response of the sensor to increase.